Resolutions of IAE (First International Congress of Egyptology, 1979)
Purpose To compare combined dexamethasone implant and intravitreal aflibercept (AFB) to AFB monotherapy treatment in diabetic macular edema (DME). Methods This open-label randomized clinical trial involved randomization of patients with DME (n = 50) to pro re nata treatment with combined dexamethasone and AFB or AFB alone according to prespecified retreatment criteria. Best-corrected visual acuity, central subfield retinal thickness (CST), and adverse events were monitored monthly for 48 weeks. Results The combined treatment and the AFB monotherapy group demonstrated CST reductions at each visit. The difference (95% confidence intervals [CI]) in the change from baseline in CST between the groups was -32.9 (-81.5 to 15.6) µ m at week 48, favoring the combination therapy group without significance ( P = 0.183). The difference in the change from baseline in best-corrected visual acuity was -3.3 (-9.2 to 2.5) letters read at week 48 ( P = 0.266). Injection number was numerically higher in the aflibercept monotherapy group (mean ± SD, 5.9 ± 1.8) than in the combination group (4.9 ± 1.5). The AFB monotherapy group had a 90% higher injection rate over the study period (incidence rate ratio [95% CI] = 1.9 [0.9-4.0]) without statistical significance ( P = 0.081). The combined treatment group achieved quicker time to resolution of DME (log-rank P -value = 0.013) by a median difference (95% CI) of 12 (0-24) weeks. Three eyes and two eyes in the combined therapy group developed worsening cataracts and intraocular pressure elevation requiring medical management, respectively. Conclusion Combined treatment achieved similar anatomic and visual outcomes compared with AFB monotherapy, with quicker DME resolution but higher cataract and intraocular pressure risks.